1977
DOI: 10.1111/j.2044-8279.1977.tb02338.x
|View full text |Cite
|
Sign up to set email alerts
|

Iconic Memory and Reading Performance in Nine‐year‐old Children

Abstract: Summary. 36 9‐year‐old children were given a test of image persistence in visual sensory (iconic) memory, and the Neale Analysis of Reading Ability. In the iconic memory test the subjects viewed a white disc in a tachistoscope and were required to state whether or not the disc disappeared for a short interval which ranged from 10 ms to 800 ms. The shortest disappearance perceived was taken as a measure of icon persistence. The reading test gave scores for fluency, accuracy and comprehension. All three measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

1980
1980
2001
2001

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 6 publications
(6 reference statements)
3
12
0
1
Order By: Relevance
“…Indeed, although temporal processing deficits are common in dyslexia (see Farmer & Klein, 1995, for a review), many dyslexics are not impaired in this respect either auditorily (Reed, 1989;Tallal, 1980;Tallal & Stark, 1982) or visually (Høien, 1982;Riding & Pugh, 1977-in the latter studies demonstrating even less visual persistence than good readers. Furthermore, the deficit in the temporally sensitive transient/magnocellular pathway that has been identified in many studies of dyslexia (see Lovegrove, 1996, for an overview) is not found in dyslexics manifesting dyseidetic (LL) characteristics (Borsting et al, 1996;Ridder, Borsting, Cooper, McNeel, & Huang, 1997;Slaghius & Ryan, 1999;Spinelli et al, 1997).…”
Section: Temporal Processing and Dyslexiamentioning
confidence: 97%
“…Indeed, although temporal processing deficits are common in dyslexia (see Farmer & Klein, 1995, for a review), many dyslexics are not impaired in this respect either auditorily (Reed, 1989;Tallal, 1980;Tallal & Stark, 1982) or visually (Høien, 1982;Riding & Pugh, 1977-in the latter studies demonstrating even less visual persistence than good readers. Furthermore, the deficit in the temporally sensitive transient/magnocellular pathway that has been identified in many studies of dyslexia (see Lovegrove, 1996, for an overview) is not found in dyslexics manifesting dyseidetic (LL) characteristics (Borsting et al, 1996;Ridder, Borsting, Cooper, McNeel, & Huang, 1997;Slaghius & Ryan, 1999;Spinelli et al, 1997).…”
Section: Temporal Processing and Dyslexiamentioning
confidence: 97%
“…The pattern for the easy and difficult passages is similar for listening, but different for reading. The pattern for reading is similar in the difficult passage to the inverted V relationship previously found by Riding & Pugh (1977). In earlier investigations subjects were taken to the limit of their abilities in that they were required to read progressively more difficult passages until they were constantly failing.…”
Section: Sexmentioning
confidence: 88%
“…Riding & Pugh, 1977). The subjects viewed a 1 cm diameter white disk on a black background in an Electronics Developments twofield tachistoscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is the need for scientific evidence that would validate the concept of Scotopic Sensitivity Syndrome. The following sources were reviewed and synthesized in an effort to address this issue: Bassi and Lehmkuhle (1990); Blakeslee (1991); Breitmeyer and Ganz (1976); Fricker (1989); Garzia and Nicholson (1990); Livingstone, Rosen, Drislane, and Galaburda (1991); Lovegrove, Martin, and Slaghuis (1984);Reeves (1988); Riding and Pugh (1977); Sackitt (1976); Suchoff (1981); Williams and LeCluyse (1990). Insights of other writers were interjected where relevant to this subtopic.…”
Section: Scope Of the Reviewmentioning
confidence: 99%